ANALISIS PENGARUH EVA (ECONOMIC VALUE ADDED) DAN MVA (MARKET VALUE ADDED) TERHADAP HARGA SAHAM PADA PERUSAHAAN MIGAS YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2018-2022 - Hayyu Puspita Dewi; Fitri Dwi Jayanti (Jurnal Ekonomi, Manajemen dan Akuntansi (JEMA) Universitas Ngudi Waluyo, 2024)
This study aims to analyze and determine the effect of EVA (Economic Value Added) and MVA (Market Value Added) on stock prices in oil and gas companies listed on the Indonesia Stock Exchange in 2018-2022. The sampling of this study used the Purposive Sampling method and obtained samples from 10 companies. The results of this study show that partially or Test T, EVA (Economic Value Added) has a significant positive effect on stock prices, MVA (Market Value Added) has a significant positive effect on stock prices. Meanwhile, simultaneously or Test F, EVA (Economic Value Added) and MVA (Market Value Added) have a significant effect on stock prices with a coefficient of determination (Adjusted R-Square) of 0.321. This means that 32.1% of the independent variables EVA and MVA affect the stock price, while the remaining 67.9% are influenced by other factors.